Ischemic Heart Disease Diagnosed Before Sudden Cardiac Arrest Is Independently Associated With Improved Survival. Issue 5 (6th October 2014) - Stecker, Eric C.; Teodorescu, Carmen; Reinier, Kyndaron; Uy‐Evanado, Audrey; Mariani, Ronald; Chugh, Harpriya; Gunson, Karen; Jui, Jonathan; Chugh, Sumeet S.
Abstract : Background: Sudden cardiac arrest (SCA) is a significant public health problem, and rates of survival after resuscitation remain well below 10%. While several resuscitation‐related factors are consistently associated with survival from SCA, the impact of specific comorbid conditions has not been assessed. Methods and Results: The Oregon Sudden Unexpected Study is an ongoing, multisource, community‐based study in Portland, Oregon. Patients with SCA who underwent attempted resuscitation between 2002 and 2012 were included in this analysis if there were both arrest and prearrest medical records available. Information from the emergency medical services system, medical examiner, public health division, hospitals, and clinics was used to adjudicate SCA, evaluate comorbidities, and identify medical treatments. Univariate and multivariate analyses were performed to investigate the influence of prearrest comorbidities on survival to hospital discharge. Among 1466 included patients, established resuscitation‐related predictors (Utstein factors) were associated with survival, consistent with prior reports. When a panel of prearrest comorbidities was evaluated along with Utstein factors, recognized coronary artery disease was significantly associated and predicted higher odds of survival (unadjusted odds ratio 1.5, P <0.001; adjusted odds ratio 1.5, P =0.02). In multivariable logistic models, prearrest coronary artery disease modified the survival effects of bystander cardiopulmonary resuscitation, but did not modify other Utstein factors. Conclusions: An established diagnosis of coronary artery disease was associated with 50% higher odds of survival from resuscitated SCA after adjustment for all arrest‐related predictors. These findings raise novel potential mechanistic insights into survival after SCA, while highlighting the importance of early recognition and treatment of coronary artery disease.